2018
DOI: 10.1039/c8ra01723a
|View full text |Cite
|
Sign up to set email alerts
|

Production of renewable long-chained cycloalkanes from biomass-derived furfurals and cyclic ketones

Abstract: a Developing renewable long-chain cycloalkanes from lignocellulosic biomass is of significance because it offers huge resource storage, wide applications in aviation/diesel fuels and mitigation of CO 2 emissions.In this paper, cycloalkanes with carbon chain lengths of 13-18 were produced from biomass-derived furfural species (furfural and 5-hydroxymethylfurfural) and cyclic ketones (cyclopentanone and cyclohexanone) via aldol condensation, followed by hydrogenation to saturate the C]C and C]O bonds, and hydrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…In addition, gas products including C1–C5 light alkanes (mostly CH 4 , C 2 H 6 ,C 3 H 8 , trace butane, and pentane) were observed, and a total C1–C5 light alkane yield of 13% was obtained. These gas products were produced from an HZSM-5-catalyzed cracking reaction. , Based on complete conversion of the condensation and detected products, more than 90% of the carbon balance was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, gas products including C1–C5 light alkanes (mostly CH 4 , C 2 H 6 ,C 3 H 8 , trace butane, and pentane) were observed, and a total C1–C5 light alkane yield of 13% was obtained. These gas products were produced from an HZSM-5-catalyzed cracking reaction. , Based on complete conversion of the condensation and detected products, more than 90% of the carbon balance was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Similar high yield of derived C 9 and C 10 alkanes (gasoline) were after hydrogenation and HDO obtained of the aldol condensation products over Pd/C and Pd-FeO x /SiO 2 catalysts, respectively. In an analogous study, Liu et al [23] reported the aldol condensation of various furfural species with cyclic ketones over a NaOH catalyst and obtained high yield (>90%) of the target condensation intermediates under mild conditions (30 °C; 40 min). Afterwards, amorphous zirconium phosphate combined with Pd/C catalyzed HDO of the condensation intermediates to cycloalkanes (gasoline) in good yield (76%) at optimized reaction conditions.…”
Section: New Catalyst Systemsmentioning
confidence: 98%
“…The obtained adducts usually act as substrates for hydrogenolysis in the synthesis of biobased fuels. Simple ketones like acetone, methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone are used as enolate components . The main idea of this process is lengthening the carbon backbone of the molecule to obtain higher hydrocarbons.…”
Section: Transformations Of 5-(hydroxymethyl)furfural (Hmf)mentioning
confidence: 99%
“…Simple ketones like acetone, methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone are used as enolate components. 155 The main idea of this process is lengthening the carbon backbone of the molecule to obtain higher hydrocarbons. Various bases like CaO 156 or piperidine 157 can be applied.…”
Section: Transformations Of 5-(hydroxymethyl)furfural (Hmf)mentioning
confidence: 99%